O processo de inserção escolar precoce: a funcionalidade das relações coparentais - Pasinato, Liana (Universidade do Vale do Rio dos Sinos, 2013)
Nowadays, the entry of children in preschool involves numerous challenges. Due to the characteristics of double-work of a growing number of genitors, and the shortage of social support network, this period has was reduced, since children are going to schools right after the end of maternity leave. The parents need to tackle this overlapping of two stages of family life cycle, which are the transition from conjugality to parenting, and coparenting and children entering the kindergarten. Given that the articulation of these relationships might be expressed in difficulties for the children at this time. In this regard, the aim of this dissertation was to comprehend how the coparenting sets up in couples where the children were enrolled to the childhood education, right after the end of maternity leave. This dissertation is composed of 6 two empirical articles, the first titled "The transition to coparenting: couples where their children were enrolled to the school at the end of maternity leave " and the second "The coparenting in families with babies who have indicatives of early school insertion difficulties". An exploratory and descriptive study was made, with four nuclear families, living in Erechim / RS, aged between 26 and 40 years, and where the children had entered the kindergarten soon after the end of maternity leave. The instruments used were: sociodemographic questionnaire, semistructured script and interview about coparenting. The results of this study show important aspects in the family dynamics of these couples during the early school insertion of its children. The findings show changes of the present time that have an impact in this moment, such as the difficulty for the family to find a support network, the valuation of financial income of women, and for this reason enroll children to school earlier. These characteristics are expressed in the fact of the coparenting is performed more equally by the couples of this study, since double-work and the inclusion of children prematurely in school impose that dynamic. However, in the process of school integration, mothers are still the main participants, pointing a heterogeneity in these dynamics. Just as household tasks are not equally divided, and are associated with gender roles.
Keywords: Parentalidade; Coparentalidade; Inserção Escolar; Duplo-trabalho; Parenting; Co-parenting; School integration; Double-work; ACCNPQ::Ciências Humanas::Psicologia